Planktotrons: A novel indoor mesocosm facility for aquatic biodiversity and food web research. (27th June 2017) - Gall, Andrea; Uebel, Udo; Ebensen, Uwe; Hillebrand, Helmut; Meier, Sandra; Singer, Gabriel; Wacker, Alexander; Striebel, Maren
Abstract: We established a new indoor mesocosm facility, 12 fully controlled "Planktotrons", designed to conduct marine and freshwater experiments for biodiversity and food web approaches using natural or artificial, benthic or planktonic communities. The Planktotrons are a unique and custom‐tailored facility allowing long‐term experiments. Wall growth can be inhibited by a rotating gate paddle with silicone lips. Additionally, temperature and light intensity are individually controllable for each Planktotron and the large volume (600 L) enables high‐frequency or volume‐intense measurements. In a pilot freshwater experiment various trophic levels of a pelagic food web were maintained for up to 90 d. First, an artificially assembled phytoplankton community of 11 species was inoculated in all Planktotrons. After 22 d, two ciliates were added to all, and three Daphnia species were added to six Planktotrons. After 72 d, dissolved organic matter (DOM, an alkaline soil extract) was added as an external disturbance to six of the 12 Planktotrons, involving three Planktotrons stocked with Daphnia and three without, respectively. We demonstrate the suitability of the Planktotrons for food web and biodiversity research. Variation among replicated Planktotrons ( n = 3 minimum) did not differ from other laboratory systems and field experiments. We investigated population dynamics and interactions among the different trophic levels, and found them affected by the sequence of ciliate and Daphnia addition and the disturbance caused by addition of DOM.